Alat Uji Emisi Portabel Kendaraan Bermotor - Pandu Aldhareva; Risfendra Risfendra (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
This paper purpose to created a portable vehicle emission test equipment equipped with a data logger system, where the measurement data obtained are stored on a micro-SD card. Vehicle emission protection test equipment issued consists of hardware and software. The hardware part consists of a mechanical construction and an electronic circuit consisting of a power supply circuit, sensor MQ-7, RTC DS1307, 4x3 keypad. Micro-SD card, LCD 16x2, buzzer and Arduino UNO. The software part consists of the Arduino IDE programming and system flowchart. Results of CO gas measurements with a portable emission test device are stored on a memory card in the order of the registration number and the date also time the measurement process was carried out. The CO gas level of the vehicle gets smaller on the Injection type engine system with Pertamax or Pertalite type fuel, otherwise the CO gas level will be even greater when using the  carburetor type engine system with premium fuel.